Green Finance and Corporate Performance in State-Owned Banks - Indra Kusumo; Abdul Basyith (Training & Research Institute - Jeramba Ilmu Sukses, 2026)
The problem formulated in this study is whether green finance affects firm value. The green finance indicator is seen from the total and non-MSME KKUB. Indicators of company value include ROA, ROE, and stock returns. The population of this study is all state-owned banks that apply KKUB, namely BRI, BNI, BTN, BSI, and Mandiri. The samples used were four state-owned banks selected by sampling, namely BRI, BNI, BTN, and Mandiri for 2019-2021. Secondary data are used as the basis for analysis, and data collection techniques include content analysis. The analytical techniques employed are Financial Analysis, Data Normality Testing, Descriptive Statistics, and simple linear regression. The results of the analysis show that total green finance has a positive and significant effect on ROE, and non-MSME green finance has a positive and significant effect on ROE and stock returns. Meanwhile, total and non-MSME green finance have no positive effect on ROA, and total green finance has no positive effect on stock returns